Scleral necrosis after brachytherapy of uveal melanoma and methods of its elimination - S. V. Saakyan; A. G. Amiryan; V. V. Valskiy; I. S. Mironova; E. N. Iomdina; G. A. Markosyan (Российский офтальмологический журнал)
Purpose: To analyze the results of scleroplastic operations aimed at eliminating radiation necrosis of the sclera in patients who underwent brachytherapy (BT) of uveal melanoma (UM) using a variety of plastic materials. Material and methods. The paper presents the results of treatment of 19 patients aged 32 to 67 years with radiation necrosis of the sclera after BT of UM. Scleroplasty was carried out 3 to 33 months (the median being 15 months) after brachytherapy using cadaveric sclera (13 patients), alloplant from the dura mater (3 patients) and synthetic ophthalmic material (4 patients). Results. On the whole, the materials and methods used for scleroplasty are effective and most cases save the patient’s eye (17 of 19 eyes have been saved)., However, they are imperfect, which requires that new materials and new methods of eliminating post-radiation defects of the sclera be elaborated and introduced into clinical practice. Conclusion. When planning and performing sclero plasty, strict individual approachs required. The operations have to be performed only in specialized ophthalmic hospitals in cases, of clear indications to uveal melanoma radiotherapy. Preventive measures should always be taken with regard to patients with a risk of necrosis, which will help reduce the frequency and severity of radiation sclera necrosis // Russian Ophthalmological Journal, 2017; 1: 43-8. doi: 10.21516/2072-0076-2017-10-1-43-48.